2012
DOI: 10.1080/10538720.2012.697039
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Research with Lesbian, Gay, and Bisexual Populations: Navigating Research Ethics Board Reviews

Abstract: The acceleration of research with lesbian, gay, and bisexual (LGB) populations amid existing sexual prejudice and advancing human rights leads to sometime conflicting stances between researchers and ethics boards over acceptable methodological practices. Ethics boards, charged with ensuring the safety of research participants, may engage in ostensibly protective stances regarding potential risks and informed consent that are unwittingly founded upon negative stereotypes of LGB populations. We examine four case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Furthermore, ethics research can help determine adolescents’ capacity to consent to various research methodologies. Without such evidence to guide their decisions, IRBs must rely on subjective judgments; if they believe that study‐related discomfort will be greater than discomfort encountered in everyday life or during routine physical or psychological examinations, the study is considered to pose “greater than minimal risk.” Ethics research can assess the extent of research risks and help identify appropriate safeguards (e.g., having an adult serve as a youth advocate when parental permission requirements are waived).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ethics research can help determine adolescents’ capacity to consent to various research methodologies. Without such evidence to guide their decisions, IRBs must rely on subjective judgments; if they believe that study‐related discomfort will be greater than discomfort encountered in everyday life or during routine physical or psychological examinations, the study is considered to pose “greater than minimal risk.” Ethics research can assess the extent of research risks and help identify appropriate safeguards (e.g., having an adult serve as a youth advocate when parental permission requirements are waived).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we found that 68% of SGM youth who were not out would refuse to participate in a biomedical HIV prevention study that required guardian permission for these reasons (Fisher, Arbeit, Dumont, Macapagal, & Mustanski, 2016). In both cases, investigators attempting to increase SGM youth’s representation in sexual health survey research may face challenges recruiting unbiased samples of youth if guardian permission is not waived, thereby limiting the generalizability of findings to SGM youth whose parents are accepting of their sexuality and gender identity (Fisher & Mustanski, 2014; Mustanski, 2011; Tufford, Newman, Brennan, Craig, & Woodford, 2012). In addition, investigators may be more inclined to exclude SGM adolescents from sexual health research due to anticipated or actual difficulties obtaining IRB approval or waivers of guardian permission (Miller, Forte, Wilson, & Greene, 2006; Mustanski, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, exceptions may exist "when this conflicts with youths' emerging desire for privacy and independence" ( Denissen et al, 2010, p. 570), or when seeking parental consent may put the adolescent at unnecessary risk. For example, asking LGBTQ youths under 18 years of age to provide parental consent to their participation in research inquiries could put participants at significant risk if their parents are unaware or unsupportive of their LGBTQ status, and may result in less diverse samples ( Elze, 2003;Mustanski, 2011;Tufford, Newman, Brennan, Craig, & Woodford, 2012). This issue of parental knowledge and support may also apply to other populations of youths (for example, youths who are homeless or youths engaging in illegal or risky behavior).…”
Section: Consentmentioning
confidence: 99%